PENILAIAN PASAR SEHAT DI PASAR TRADISIONAL JOMBANG DAN PASAR MODERN BINTARO TAHUN 2023 - Tiara, Faudylawati (2023)
The market is a meeting place for people to get their daily needs and the market can potentially be a place for disease transmission and a breeding ground for vectors. The condition of the market environment must be considered in order to avoid disease by conducting a healthy market assessment. Jombang traditional market and Bintaro modern market are markets that are often visited by people in South Tangerang City. This study is a qualitative research with Rapid Assessment Procedure (RAP) design conducted in February - June 2023. Data were collected using a checklist sheet for observation and interview guidelines for 2 key informants (WM) and 62 main informants from 3 categories (FGD). The selection of informants was carried out using purposive sampling method. The results obtained in the Jombang traditional market have not met the requirements with a value of 36.73% because of the facilities and buildings, vector control and disease-carrying animals, waste management and waste management are not appropriate. The Bintaro modern market has met the requirements with a value of 87.75%. The conclusion is that the Jombang traditional market cannot be said to be a healthy market because there are still aspects of the assessment that have not met the requirements, while the Bintaro modern market can be said to be a healthy market because almost all aspects meet the requirements in accordance with Permenkes RI 17 of 2020 concerning healthy markets.